TRANSLITERASI NASKAH MANUSKRIP JAWA: UPAYA NYATA PENYEDIAAN BAHAN PEMBELAJARAN DAN PENELITIAN KEBUDAYAAN JAWA - - Mulyana (JURNAL IKADBUDI, 2013)
The aim of research is give lesson materials and research about Javanese manuscripts. The method used to explore manuscript is transliteration. Namely, transfering from source letter to target letter, and more transliteration from old Javanese language to Indonesian language.The reaearch desaign is R and D (research and development). The subject matter are students of Ekspresi Tulis Lanjut , in class G, H, and A in javanese department. The collecting of data used to observation, dokument analysis, and tasks. The object of research is Javanese manuscripts as the result of translation in the class.The results of this research are materials javanese manuscripts, namely: (1) serat Darma laksita, (2) Serat Kudhup sari, and (3) Serat Kumandaka. The third of Javanese manuscripts contens etics, relegion and aestetic that very important for lesson and research. The form of manuscripts are tembang Macapat and gerongan songs. The manuscripts letter can read clearly and easely. Finnaly, the results of research very important for students, teachers, lecturer, and all of academics people.Key words: javanese manuscript, transliteration